Production of WZ events in pp collisions at square root(s) = 1.96 TeV and limits on anomalous WWZ couplings. - Abazov, V; Abbott, B; Abolins, M; Acharya, B; Adams, M; Adams, T; Agelou, M; Agram, J; Ahn, S; Ahsan, M; Alexeev, G; Alkhazov, G; et al. (2005)
We present results from a search for WZ production with subsequent decay to l nu l' l' (l and l' = e or mu) using 0.30 fb(-1) of data collected by the D0 experiment between 2002 and 2004 at the Fermilab Tevatron. Three events with WZ decay characteristics are observed. With an estimated background of 0.71 +/- 0.08 events, we measure the WZ production cross section to be 4.5(-2.6)(+3.8) pb, with a 95% C.L. upper limit of 13.3 pb. The 95% C.L. limits for anomalous WWZ couplings are found to be -2.0 < delta kappaZ < 2.4 for form factor scale lambda = 1 TeV, and -0.48 < lambdaZ < 0.48 and -0.49 < delta g(1)(Z) < 0.66 for lambda = 1.5 TeV.